Pengaruh Profitabilitas dan Leverage terhadap Penghindaran Pajak dengan Ukuran Perusahaan sebagai Variabel Moderasi: Studi Kasus Tahun 2020-2022 pada Perusahaan Sektor Property and Real Estate yang Terdaftar di Bursa Efek Indonesia - Silaen, Muliadi Satar; Safrianti, Sintia; Waliamin, Janusi (IAI Nasional Laa Roiba Bogor, 2024)
This research aims to examine the influence of Profitability ratio and Leverage ratio on tax avoidance with company size as a moderating variable in the property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020-2022. It's a quantitative research with a causal nature. The population for this study consists of property and real estate sector companies listed on the IDX during 2020-2022. Sample selection was done using purposive sampling method. Data sources included secondary data such as company financial reports. Data collection techniques involved documentation and literature study. Data analysis techniques used were descriptive statistical analysis, classic assumption testing, multiple linear regression analysis, and hypothesis testing. The research results indicate that the Profitability ratio (ROA) has a significant negative impact on tax avoidance, while the Leverage ratio (DER) does not affect tax avoidance. Company size (SIZE) strengthens the impact of Profitability ratio (ROA) on tax avoidance, but it does not strengthen the impact of Leverage ratio (DER).